Aeroacustic and Vibroacoustic Advancement in Aerospace and Automotive Systems - Citarella, Roberto; Federico, Luigi; Mattia, Barbarino (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
This Special Issue highlights the latest enhancements in the abatement of noise and vibrations in aerospace and automotive systems. The reduction of acoustic emissions and the improvement of interior cabin comfort desired by all major transportation industries, as these areas have a direct impact on customer satisfaction and, consequently, the commercial success of new products. Topics covered in this Special Issue deal with computational approaches, instrumentation and data analysis related to noise and vibrations of fixed-wing aircraft, satellites, spacecraft, automobiles, and trains, covering aerodynamically generated noise, engine noise, sound absorption, cabin acoustic treatments, duct acoustics, and vibroacoustic properties of materials. This Special Issue also focuses on industrial aspects. Existing procedures and algorithms that are useful in reaching the abovementioned objectives in the most efficient way are illustrated in the collected papers.